Accidental mechanical asphyxia of children in Germany between 2000 and 2008 - Meyer, Frauke; Zimmer, Gisela (International journal of legal medicine, 2012)
Accidents constitute one of the greatest risks to children, yet there are few medical reports that discuss the subject of accidental asphyxia. However, a systematic analysis of all documented cases in Germany over the years 2000-2008 has now been conducted, aiming at identifying patterns of accidental asphyxia, deducing findings, defining avoidance measures and recommending ways of increasing product safety and taking possible precautions. The analysis is based on a detailed retrospective analysis of all 91 relevant autopsy reports from 24 different German forensic institutes. A variety of demographic and morphological data was systematically collected and analysed. In 84 of the 91 cases, the sex of the victim was reported, resulting in a total of 57 boys (68 %) and 27 girls (32 %). The age spread ranged between 1 day and 14 years, with an average of 5.9 years. Most accidents occurred in the first year of life (20 %) or between the ages of 1 and 2 years (13 %). In 46 % of cases, the cause of death was strangulation, with the majority occurring in the home environment. In 31 % of all cases, the cause of death was positional asphyxia, the majority resulting from chest compression. In 23 % of cases, the cause of death was aspiration, mainly of foreign bodies. Today, accidental asphyxiation is a rare cause of death in children in Germany. Nevertheless, the majority of cases could have been avoided. Future incidence can be reduced by implementing two major precautions: increasing product safety and educating parents of potentially fatal risks. Specific recommendations relate to children’s beds, toys and food.
Gesehen am 28.11.2018